Perbedaan Tingkat Kebugaran Jasmani Mahasiswa Prodi Teknik Kimia UPN “Veteran” Yogyakarta Kuliah Olahraga II Cabang Senam dan Bola Voli - Sumintarsih Sumintarsih; Hanafi Mustofa (Publikasi Indonesia, 2022)
This study aims to determine: 1) The effect of gymnastics on the level of physical fitness of students of the Chemical Engineering Study Program UPN